Analysis of Student Perceptions of Teaching Campus Participants - Eduward Situmorang (Pusdikra-Publishing.com, 2024)
The Independent Campus Learning (MBKM) policy provides students with the opportunity to take part directly in society to solve the country's problems. The Teaching Campus is one of the MBKM programs with the aim of solving educational literacy and numeracy problems in Indonesia. The research in this article aims to describe the impact of implementing the MBKM program, namely the 6th Teaching Campus organized by the Ministry of Education and Culture, which comes from students from HKBP Nommensen Pematangsiantar University. The research used mixed methods. Quantitative data in this research includes questionnaires from teaching campus school partners and students participating in teaching campuses. The research data is in the form of perception interviews from students participating in the teaching campus class 6. Based on the research results, it is known that students' perceptions after attending the teaching campus are very good, namely on average 90%. This is in line with the partner's high perception of the quality and abilities of students, namely 93%. Based on student perceptions, campus teaching programs not only provide classroom teaching experience and literacy and numeracy skills but can also help improve students' collaboration abilities and soft skills.